Magnetic resonance imaging in schizophrenia: Luxury or necessity? (Review) - Iliuta, Floris Petru (Exp Ther Med, 2021)
Schizophrenia, one of the most common psychiatric disorders, with a worldwide annual incidence rate of approximately 0.3-0.7%, known to affect the population below 25 years of age, is persistent throughout lifetime and includes people from all layers of society. With recent technological progress that allows better imaging techniques, such as the ones provided by computed tomography and particularly magnetic resonance imaging (MRI), research on schizophrenia imaging has grown considerably. The purpose of this review is to establish the importance of using imaging techniques in the early detection of brain abnormalities in patients diagnosed with schizophrenia. We reviewed all articles which reported on MRI imaging in schizophrenia. In order to do this, we used the PubMed database, using as search words ‘MRI’ and ‘schizophrenia’. MRI studies of first episode patients and chronic patients, suggest reduction of the whole brain volume. Enlargement of lateral ventricles was described as positive in 15 studies out of 19 and was similar to findings in chronic patients. Moreover, for the first episode patients, all data collected point to important changes in medial temporal lobe structures, diminished hippocampal volume, the whole frontal lobe, asymmetry in prefrontal cortex, diminished volume in cingulate, corpus callosum, and cavum septum pellucidum reported abnormalities. MRI is recommended as an important tool in the follow-up process of patients with schizophrenia. Yet, it is still under debate whether the abnormalities described in this condition are able to be used as diagnostic biomarkers.